Cloning, expression and purification of D-Tyr-tRNATyr-deacylase from Thermus thermophilus - Rybak, M.Yu.; Kovalenko, O.P.; Kryklyvyi, I.A.; Tukalo, M.A. (Вiopolymers and Cell, 2015)
D-Tyr-tRNATyr-deacylase (DTD) is a conservative enzyme, found in all domains of life, which ensures an additional checkpoint in the recycling of misaminoacylated D-Tyr-tRNATyr. DTD is capable of accelerating the hydrolysis of the ester linkage of D-Tyr-tRNATyr producing a free tRNA and D-tyrosine, thereby preventing an incorrect incorporation of D-amino acids into proteins. Deacylase distinguishes between D- and L-aminoacyl moieties and does not hydrolyze L-aminoacylated tRNA. The structural bases of this specificity and the mechanism of D-aminoacyl-tRNA hydrolysis are poorly understood. Aim. To clone D-Tyr-tRNATyr-deacylase from T. thermophilus (DTDTT), optimize the conditions for its expression in E.coli and develop an efficient purification procedure yielding the high quality enzyme suitable for the structural and functional studies. Methods. For amplification of DTD gene from T. thermophilus genomic DNA and its cloning into the pProEXHTb expression vector modern techniques were applied. Purification of the recombinant DTD protein was done with three types of column chromatography. His-tag was cleaved out from DTD by TEV protease. The cleavage was confirmed by Western blot analysis with anti-His-tag antibodies. Molecular weight of purified DTDTT was determined by the gel-filtration. Results. The expression construct pProEXHTb, containing DTD sequence from T. thermophilus, was obtained and successfully expressed in the BL21(DE3)pLysS E.coli strain. The protein of interest was purified to homogeneity by the combination of affinity (Ni-NTA), anion-exchange (Q-Sepharose) and size-exclusion (Superdex S 200) chromatographies. 2 mg of more than 90% pure recombinant DTD can be obtained from 1 L of bacterial culture. Molecular weight of purified DTD from T. thermophilus was determined to be 32 kDa, suggesting its dimeric structure. Conclusions. The pProEXHTb expression vector can be used for expression of DTD from T. thermophilus. The preparative amounts of DTD can be obtained after the three-step chromatographic procedures and used for further functional and structural studies.